Singlet molecular oxygen generation by light-activated DHN-melanin of the fungal pathogen Mycosphaerella fijiensis in black Sigatoka disease of bananas. - Miguel J Beltrán-García; Fernanda M Prado; Marilene S Oliveira; David Ortiz-Mendoza; Alexsandra C Scalfo; Adalberto Pessoa; Marisa H G Medeiros; James F White; Paolo Di Mascio (PLoS ONE, 2014)
In pathogenic fungi, melanin contributes to virulence, allowing tissue invasion and inactivation of the plant defence system, but has never been implicated as a factor for host cell death, or as a light-activated phytotoxin. Our research shows that melanin synthesized by the fungal banana pathogen Mycosphaerella fijiensis acts as a virulence factor through the photogeneration of singlet molecular oxygen O2 (1Δg). Using analytical tools, including elemental analysis, ultraviolet/infrared absorption spectrophometry and MALDI-TOF mass spectrometry analysis, we characterized both pigment content in mycelia and secreted to the culture media as 1,8-dihydroxynaphthalene (DHN)-melanin type compound. This is sole melanin-type in M. fijiensis. Isolated melanins irradiated with a Nd:YAG laser at 532 nm produced monomol light emission at 1270 nm, confirming generation of O2 (1Δg), a highly reactive oxygen specie (ROS) that causes cellular death by reacting with all cellular macromolecules. Intermediary polyketides accumulated in culture media by using tricyclazole and pyroquilon (two inhibitors of DHN-melanin synthesis) were identified by ESI-HPLC-MS/MS. Additionally, irradiation at 532 nm of that mixture of compounds and whole melanized mycelium also generated O2 (1Δg). A pigmented-strain generated more O2 (1Δg) than a strain with low melanin content. Banana leaves of cultivar Cavendish, naturally infected with different stages of black Sigatoka disease, were collected from field. Direct staining of the naturally infected leaf tissues showed the presence of melanin that was positively correlated to the disease stage. We also found hydrogen peroxide (H2O2) but we cannot distinguish the source. Our results suggest that O2 (1Δg) photogenerated by DHN-melanin may be involved in the destructive effects of Mycosphaerella fijiensis on banana leaf tissues. Further studies are needed to fully evaluate contributions of melanin-mediated ROS to microbial pathogenesis.